PENGEMBANGAN MODUL BERBASIS DISCOVERY LEARNING DISERTAI NILAI KARAKTER BERBANTU QR CODE PADA MATERI PENCEMARAN LINGKUNGAN UNTUK SISWA KELAS X - Mely Diana Rosa; Muhfahroyin Muhfahroyin; Triana Asih (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
The purpose of this development research is to produce a product in the form of a discovery learning-based module with appropriate QR Code-assisted character values ​​so that it can be used by students and increase knowledge. This type of development research using 4D models initiated by Thiagarajan, Sammel and Sammel (1974). This 4D development model has four stages, namely define, design,develop and desseminate, but in development research it only reaches the develop stage. The product that has been developed by this researcher has been validated by design experts, getting a percentage of 93% with the